Anatomy by whole body dissection: a new Masters of Surgery course. Issue 9 (25th April 2016) - Burgess, Annette; Ramsey‐Stewart, George; Mellis, Craig
Abstract : Background: In 2012, a new anatomy by whole body dissection‐Masters of Surgery (WBD‐MS) course was introduced as a subject within the MS degree at Sydney Medical School. The purpose of this study, based on two iterations of the course, implemented in 2012 and 2013, was to investigate the participants' knowledge acquisition of clinical topographical anatomy and perceptions of the course. Methods: During 2012 and 2013, a total of 26 postgraduate surgical trainees enrolled in the WBD‐MS course. Each cohort participated in a 34‐day dissection course over 12 weeks. Within each course, two groups of six to seven students were allocated to two cadaver subjects. A rigid teaching, assessment and dissection schedule was followed. Supervision was by nine specialist surgeons, who were present for their areas of expertise. The effectiveness of the course was assessed by knowledge acquisition and retention. Students' perception of the course was assessed by questionnaire and focus groups. Results: The course produced a marked increase in participants' topographical anatomical knowledge. Results of assessments of participants in a standardized practical examination were 8/20 median pre‐course, and 19/20 median at the end of the course. These results were statistically significant. Participants identified three outstanding features of the course: (i) the presence of surgeons as supervisors; (ii) the course structure and design; and (iii) the small class size and team learning methods. Conclusion: The dissection course provided a significant increase in the acquisition of three‐dimensional regional relational topographical anatomical knowledge. The presence of surgical specialists as supervisors, and the course design prompted effective student engagement in learning and understanding.